The Focus of Grammar in International Examinations - Stephenie O. Busbus; John Rey Osben Pelila; Lyzel A. Tabag; Aubrae Frances E. Bannawi; Julsen L. Copete; Frances Corrine D. Bonilla (Halu Oleo University, 2021)
Studies have proven that teaching grammar plays a significant role in teaching of English language. However, there is a need for teachers to know what to focus in teaching grammar because of its complexity in most international examinations. Therefore, the present study aimed at knowing the different focuses in teaching grammar in some of the known international examinations like IELTS, TOEFL, OET, and PTE. The researchers employed a systematic literature review where studies on this area were appraised guided by inclusion-exclusion criteria, and it was found out that there were four (4) primary areas that teachers need to ponder in teaching grammar - syntactic grammar, parts of speech, word choice, and dialect variation. Moreover, it was suggested that teachers need to revisit the practices and approaches they employed in the teaching-learning process of English in general and review all existing English criteria and tools that quantify their content knowledge.